Ultrasonographic imaging study on abdominal organs of goat - Muhamad, Siti Noraziran (2016)
This study summarizes the ultrasonographic findings of the abdominal organs of goat. Five apparently healthy does were selected in this study. All animals were non-sedated, restrained in standing position and examination area was clipped and shaved prior investigation. Rumen, reticulum, omasum, abomasum, liver, gall bladder, spleen and kidney were examined using SonoScape ultrasound scanner attached to a probe with frequency between 4.0-7.0 MHz. Examination was done using both, linear and convex transabdominal probe. From the result, rumen and spleen were examined on the left side while the other organs were examined on the right side. Rumen wall was examined and identified at the left flank area while spleen was examined at the 11th intercostal space (ICS) and the splenic vessel is rarely can be seen. For the reticulum, its wall was examined at the ventral abdomen at the 6th ICS just caudal to the xiphoid and the abomasum wall was examined at the ventral part of the 7th ICS while for the omasum, it was examined at the 8th ICS. Liver was examined from the 7th -12th intercostal spaces (ICSs) with hepatic and portal vein can be examined. Kidney was examined just caudal to the last rib while gall bladder was examined on the right side at 10th ICS. In conclusion, ultrasound examination is more convenient to be used in small ruminant medicine as an aid in the diseases diagnosis as well as evaluation of the internal organs.